Microbiostratigraphy, Microfacies and Depositional Environment of the Sarvak Formation in Bi Bi Hakimeh Oil Field (Well No. 29), Southwest Iran - Rikhtegarzadeh, M; Vaziri, S.H; Aleali, M; Bakhtiar, H Amiri; Jahani, D (International Journal of Geography and Geology, 2016)
The Sarvak Formation in Bi Bi Hakimeh oil field (well No.29) with the thickness of 324 m consists of limestone in Cenomanian - Turonian period. The upper boundary of the Sarvak Formation is in the form of disconformity with the Gurpi Formation. The lower boundary of Sarvak Formation is not clear because of lack of sequential excavation. According to microbiostratigraphy studies, 4 genera and 2 species of planktonic foraminifera and 22 genera and 28 species of benthic foraminifera are identified and based on them, three biozones were introduced including Nezzazata–Alveolinids assemblage zone, Rudist debris, and Oligosteginid facies. The zones are in consistence with zones introduced by Wynd (1965). In the study area (southwest of Iran), the Sarvak Formation is subdivided into 8 microfacies that are distinguished by petrographic analysis on the basis of their depositional textures and fauna. In addition, four major depositional environments were identified in the Sarvak Formation. These include shelf lagoon, platform margin, slope and basin environmental settings, which are interpreted as a carbonate shelf without an effective barrier separating the platform from the open ocean.